Advancing grid integration with redox flow batteries: an engineering and economic review - Mohammad Mominur Rahman; Md Maidul Islam; Md Shafiullah; Md. Ariful Islam; Mohammed Arfat Raihan Chowdhury; Md. Hasan Zahir (Green Chemistry Letters and Reviews)
The widespread use of fossil fuels, along with rising environmental pollution, has underlined the critical need for effective energy storage technologies. Redox flow batteries (RFBs) have emerged as attractive technologies due to their affordability, high safety standards, stability, tolerance of temperature extremes, and flexibility. They offer independent scalability in two dimensions (capacity (kW-h) and in power (kW)), making them highly adaptable and facilitating seamless integration with renewable technologies. This review paper emphasized the last two advantages which have not been systematically studied yet. This study offers a thorough examination of the engineering elements of RFBs, with an emphasis on their integration into grid-scale energy storage systems. The comparative techno-economic study looks at several RFB chemistries, including aqueous and non-aqueous systems, as well as recent advances in cell-level components. The article examines the role of RFBs in minimizing the variability of renewable energy supplies, improving the cost-effectiveness of existing infrastructure, and providing useful grid services. Furthermore, the paper highlights future research goals and problems in the sector, providing insights into the development and implementation of RFBs for long-term grid integration.